2013
DOI: 10.1186/1476-069x-12-95
|View full text |Cite
|
Sign up to set email alerts
|

Association between environmental factors and current asthma, rhinoconjunctivitis and eczema symptoms in school-aged children from Oropeza Province – Bolivia: a cross-sectional study

Abstract: BackgroundIn recent years, the prevalence of asthma, rhinoconjunctivitis and eczema symptoms in childhood has considerably increased in developing countries including Bolivia, possibly due to changes in lifestyle, environmental and domestic factors. This study aimed to assess the association between environmental factors and asthma, rhinoconjuctivitis and eczema symptoms in school-aged children from Oropeza Province in Chuquisaca, Bolivia.MethodsA cross-sectional study was performed in 2340 children attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Moreover, the SPT result regarding dog hair confirmed this finding. These findings are in accordance with previous studies in Bolivia [ 7 ] and Senegal [ 22 ]. The role of exposure and sensitization to dog’s allergens is unclear.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, the SPT result regarding dog hair confirmed this finding. These findings are in accordance with previous studies in Bolivia [ 7 ] and Senegal [ 22 ]. The role of exposure and sensitization to dog’s allergens is unclear.…”
Section: Discussionsupporting
confidence: 94%
“…The causes of the evolving epidemic are not entirely understood. Some suggestions are related to changes in lifestyle and environmental exposures [ 7 , 8 ] that trigger the immune system in early stages of life [ 9 ]. There is some evidence of an association between environment factors such as air pollution [ 10 ], indoor and outdoor allergens, and pollutants and the initiation and aggravation of asthma [ 1 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence differences of asthma and wheezing are diminishing. As there is an observed increase in prevalence in areas where prevalence was previously low, the global burden of asthma and wheezing, however, continues to increase [ 1 3 ]; with the most significant increase noted among children between one to five years [ 4 , 5 ]. Due to difficulties in demonstrating airflow limitation [ 6 , 7 ] in young children, it is recommended to avoid the term ‘asthma’ in preschoolers with wheezing and airway inflammatory reactions and to use the term ‘wheezing illnesses’ instead [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Bolivia, considerable sociocultural and educational differences have been reported, especially between urban and rural areas. The large difference found for current asthma symptoms between WQ (17%) and VQ (6%) could be explained by the lack of knowledge, especially in rural areas) of the written terms causing over reporting of symptoms as has been previously suggested [14,32]. But, on the other hand the video scene could explore presence of more severe asthma symptoms in comparison with WQ [19,33].…”
Section: Discussionmentioning
confidence: 87%
“…Methodology of this study has been reported previously [14,15]. A number of 43 educational establishments were selected randomly and invited to participate from a total of 185 schools listed in the Regional Education Service (SEDUCA -Chuquisaca).…”
Section: Study Subjectsmentioning
confidence: 99%